2013
DOI: 10.1007/s12291-013-0378-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention as a Cause of Hyponatremia in an Elderly Man

Abstract: Hyponatremia is a common disorder in elderly and can result in changes in cognition, seizures, coma or even respiratory arrest if not recognised and treated. Syndrome of inappropriate anti diuretic hormone secretion (SIADH) is the most common cause of hyponatremia in elderly hospitalised patients and in most cases the etiology cannot be determined on routine investigations. We present a 76 year old male with symptomatic hyponatremia who had chronic urinary retention due to a urethral stricture. His sodium leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
2
10
0
1
Order By: Relevance
“…described five elderly hospitalized patients who developed urinary retention followed by hyponatremia and confirmed SIADH. Likewise, Mahajan et al . reported a 76‐year‐old man who was diagnosed with SIADH resulting from urinary retention.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…described five elderly hospitalized patients who developed urinary retention followed by hyponatremia and confirmed SIADH. Likewise, Mahajan et al . reported a 76‐year‐old man who was diagnosed with SIADH resulting from urinary retention.…”
Section: Discussionsupporting
confidence: 83%
“…reported a 76‐year‐old man who was diagnosed with SIADH resulting from urinary retention. Interestingly, similarly to our case, this patient's sodium level normalized after catheterizing the bladder . These reports have suggested that the bladder distention associated with urinary retention can stimulate antidiuretic hormone (ADH) release from the posterior pituitary .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Existen pocos casos descritos en la literatura 3 , 4 , 5 , 6 , 7 . Se cree que la distensión vesical produce una liberación de vasopresina a nivel hipofisario 8 .…”
unclassified